A Study of Student Learning Attitudes and Motivation in Technological Processes in Learning - Nozaki, Kayoko; Wuttipong, Matsuzaki; Hiroyuki, Heman; Kawachi, Atsushi; Kawachi, Yohei (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
The influence of technological processes is something that cannot be separated from human life today, including the field of education. Students' responses and acceptance of technological processes determine the extent to which this technology can be used in the learning process. The purpose of this study was to find out how the influence of attitudes and motivation to learn from students on the process of technology in learning. This study uses a quantitative method with a survey model. The tool used in this survey model is a questionnaire on the Google form. The results found in this study are the attitudes and motivation to learn in students greatly determine the development of the technological process in learning. From this study it can be concluded that the existence of a technological process in learning will shape student character for the better and increase student motivation. The limitation of this research is that researchers only conduct research on students' attitudes and motivation in the process of technology in learning. The researcher hopes that further researchers can conduct similar research at the level of education and other subjects.